Self-regulated learning among non-Arab students: Contribution of students’ motivational belief in learning Arabic language - Mohammad Haafiz Ahmid; Mohd Khairuddin Abdullah (Quantum Academic Publisher, 2020)
Learning Arabic language among non-Arabic students is a major challenge as they do not native-speaker for the language. At the same time, they obligated to take the test and this can cause students emotional change and feel stress to achieve their goals. Self-regulated learning is one of the ways to overcome the problems because of its effectiveness in learning Arabic language. However, it can be affected by low levels of students' motivational beliefs, especially when they consider the language too difficult to learn. Therefore, this study will determine the contribution of motivational beliefs on 542 nonArab students from various Malaysian schools. A quantitative approach was adopted and a set of questionnaire was used as an instrument for data collection. Multiple regression analyzes were conducted to determine the contribution. The results revealed that students' motivational beliefs influence selfregulated learning and intrinsic value predicts the most of it. The findings demonstrate how important for students to develop their feeling towards Arabic language and built confidence so that they can practice self-regulated learning in learning Arabic language more effectively.